Is plate clearing a risk factor for obesity? A cross-sectional study of self-reported data in US adults. - Robinson, E; Aveyard, P; Jebb, SA (2014)
OBJECTIVES: Identifying eating behaviors which contribute to excess weight gain will inform obesity prevention strategies. A tendency to clear one's plate when eating may be a risk factor for obesity in an environment where food is plentiful. Whether plate clearing is associated with increased body weight in a cohort of US participants was examined. METHODS: Nine hundred and ninety-three US adults (60% male, 80% American European, mean age = 31 years) completed self-report measures of habitual plate clearing together with behavioral and demographic characteristics known to be associated with obesity. RESULTS: Plate clearing tendencies were positively associated with BMI and remained so after accounting for a large number of other demographic and behavioral predictors of BMI in analyses (β = 0.18, 95% CIs = 0.07, 0.29, P < 0.001); an increased tendency to plate clear was associated with a significantly higher body weight. CONCLUSIONS: The tendency to clear one's plate when eating is associated with increased body weight and may constitute a risk factor for weight gain.